Risk Factors for Injury to Recurrent Laryngeal Nerve in Thyroid Surgeries - A Tertiary Care Centre Experience - Ashok Kumar , Zeba Ahmed , Nasreen Naz , Ali Akber Aftab , Ashok Kumar , Zeba Ahmed , Nasreen Naz , Ali Akber Aftab (Journal of Rawalpindi Medical College, 2019)
Objective: To evaluate the risk factors of recurrent laryngeal nerve injury during thyroid surgery. Study Design: Descriptive study. Place And Duration Of Study: Department of Otorhinolaryngology-Head and Neck Surgery, Sindh Government Lyari General Hospital / Shaheed Mohatarma Benazir Bhutto Medical College and Dr Ruth K. M. Pfau Civil Hospital Karachi, Dow University of Health Sciences from July 2014 to August 2018. Methods: Every patient with goiter (multinodular / solitary nodule) admitted for primary or revision surgery with normal vocal cord movements were included in this study, while patients having hoarseness due to impaired vocal cords movements were excluded from this study. Results: Out of 120 Patients 28 (23.33%) were operated for Total Thyroidectomy, 4 (3.34%) had Near total thyroidectomy and 49(40.83%) for Right lobectomy with isthmusectomy, 35(29.17%) for Left lobectomy with isthmusectomy and 4(3.3%) cases operated for recurrent goiter. Transient unilateral vocal cord paralysis occurred in 5 cases, became permanent in 3 cases. Bilateral vocal cord paralysis was seen in revision thyroidectomy in 1 case. Conclusion: With this study we have tried to evaluate the relation of injury to RLN and type of surgery performed. It can be concluded that thyroid surgery, if performed by expert surgeons carries low risk of injury to RLN. Lobectomies have a slightly lower risk of nerve injury compared to total thyroidectomies. In revision surgeries RLN are at greater risk. Careful dissections of nerve make an important pillar in preservation of RLN during surgery. Keywords: Thyroidectomy, Recurrent Laryngeal Nerve Palsy, Risk Factors.